AIDS PREVENTION IN SUB-SAHARAN AFRICA: AS EASY AS ABC? - Bertrand, Robert L. (African Journal of Infectious Diseases (AJID), 2015)
Background: The failure to stem HIV in sub-Saharan Africa and the unique epidemiological modes of infection within this region have demonstrated that unique strategies for combatting the virus are required. This review article discusses why international AIDS campaigns in sub- Saharan Africa have largely been unsuccessful, and what, if any, strategies have worked. Methods: Articles were compiled using Web of Science and Google Scholar search engines. Results: Inspired by past successes in the West and in Southeast Asia, Western AIDS initiatives have attempted to replicate these results within the African continent through ‘risk reduction’ approaches, vying to reduce the probability of HIV transmission per coital act via physical or biochemical barriers such as condoms, male circumcision, antiretroviral therapy, post-exposure prophylactic drugs, and treatment of sexually transmitted infections. However, more than three decades of research have demonstrated that the most successful strategies were African-inspired, relied on local resources with minimal Western support, culturally relevant, and used social engineering programs that dismantled networks of sexual relationships by promoting the practice of abstinence, reducing the number of sexual partners, discouraging multiple and concurrent relationships, delaying sexual debut, and maintaining mutually monogamous relationships. Conclusion: Known through the mnemonic ‘ABC’ (Abstinence, Be faithful, Condoms), this strategy was first implemented in Uganda, yielding remarkable successes both in Uganda and thereafter in other African nations in stemming HIV. AIDS agencies should support and encourage programs that use this culturally sensitive, low cost, and effective strategy.